PERGERAKAN ISLAM DI MALAYSIA: KONTEKS DAN FAKTOR SEJARAH - Ahmad Nabil Amir; Tasnim Abdul Rahman (UIN ANTASARI BANJARMASIN, 2023)
AbstractThe paper highlights early phase of the historical development of Islamic movement in Malaysia since colonial era. This was projected from two crucial and overlapping aspects; the reform movement which brought national awareness and renewed aspiration for tajdid as well as the influence of anti-colonial movement and its underlying impact of political Islam embedded in the Malay-archipelago. It describes the impact of Islamic movement in Malaysia in fostering religious consciousness and reassertion of its dynamic spirit in broad socio-cultural and socio-political context. The pioneering work of Syed Syaikh al-Hadi, Burhanuddin al-Helmy, Ustaz Abu Bakar al-Baqir, and Syed Muhammad Naquib al-Attas has sparked significant influence and inspired profound and lasting spiritual and religious growth and struggle. The intellectual and religious movement inspired by these figures demonstrated meaningful intellectual and spiritual essence that set forth significant threshold for public debates of the Islamic moral and social premise and the dialectic of ijtihad. Their influence has brought forth progressive change that help to foster an inclusive civil society and constructed sustainable Islamic polity. This study is based on qualitative approach in the form of library research. Data collected through documentation technique and interpreted using descriptive, analytical, historical, and comparative method. This research found that the genuine struggle for Islamic cause has bring unprecedented reform in reasserting tawhid consciousness and its principal liberating values through IOK. It set forth the trajectory of realizing the objective of reform in reclaiming the spirit of ijtihad and strengthening its rational, metaphysical, and ideological basis, whose manifestation constitute the socio-political and socio-cultural faces of Islamic revival in Southeast Asia. Their foundational work has been instrumental in strengthening scientific spirit and in the proliferation of effective cadre recruited at the grassroot.Keywords: Intellectual, Islamic Movement, Malaya, Reform, Religious Thought. AbstrakKajian ini menyorot sejarah awal perkembangan gerakan Islam di Malaysia sejak zaman kolonial. Kajian ini ditinjau dari dua sudut yang penting dan bertumpang-tindih; gerakan islah yang membawa kesadaran nasional dan aspirasi pembaharuan dan tajdid serta pengaruh gerakan anti-penjajah dan kepeloporan politik Islam di rantau nusantara. Gerakan ini memunculkan kesan dan pengaruh gerakan Islam di Malaysia dalam melakukan pembaharuan dalam konteks sosio budaya dan sosio politik yang luas. Peranan dan sumbangan yang dicetuskan oleh para pelopor Islam di Malaysia seperti Syed Syeikh al-Hadi, Burhanuddin al-Helmi, Ustaz Abu Bakar al-Baqir, Syed Muhammad Naquib al-Attas dan sebagainya telah memberikan pengaruh yang signifikan dalam mengilhamkan kebangkitan dan kesedaran wa’y al-Islam yang mendalam. Gerakan Islam yang diprakarsai oleh tokoh-tokoh penting ini memperlihatkan nilai dan falsafah Islam yang ideal dan membuka ruang ijtihad yang signifikan dan segar. Pengaruh pemikiran yang dilontarkan telah menghasilkan perubahan yang progresif dalam pembentukan masyarakat madani yang inklusif dan gerakan akliah yang kuat. Kajian ini berbentuk kualitatif dengan jenis penelitian kepustakaan. Analisis konten sangat diutamakan dalam aktivitas kajian ini. Data dikumpulkan melalui metode dokumentasi dengan menerapkan kaedah analisis bercorak interpretatif, analitis, deskriptif, historis dan komparatif. Kajian ini merumuskan bahwa perjuangan dakwah yang diketengahkan telah mencetuskan perubahan yang signifikan dalam memperkokoh gerakan (harakah) dan landas (khittah) perjuangan, menggilap ruh dan semangat kebebasan, menggerakkan wacana islah dan islamisasi ilmu. Gerakan ini telah menzahirkan sumbangan dan kefahaman Islam yang tuntas dan meyakinkan dalam menggarap dasar dan arah politik dan sosio-budaya yang eksplisit, dan menzahirkan ketinggian pengaruh dan idealisme yang meluas dalam tradisi akliah dan peradaban serta upaya penggemblingan kader di semua peringkat.Kata Kunci: Gerakan Islam, Islah, Intelektual, Malaya, Pemikiran.